Operationalizing Relative Customer Value. (November 2017) - Keiningham, Timothy; Aksoy, Lerzan; Cadet, Fabienne
Abstract: The construct of "value" has been central to explaining economic exchange since the time of Adam Smith. Despite its central importance, debate still exists as to what value entails. Absent a comprehensive understanding of value, researchers and managers have grappled with how to measure and manage value. Not surprisingly, absent a definition, no comprehensive, robust approach has emerged. We argue that value first must be viewed as a dual construct, i.e. value to the customer and value to the firm, that must be balanced to be sustainable. Given that value to the customer is clearly assessed as relative to competitive alternatives, we also argue that any robust measurement of value must account for competitive alternatives. We propose applying recent research on the use of relative metrics in linking to share of category spending as the foundation of assessing value to the customer (particularly since customers in most categories divide their spending across competing firms). This allows firms to assess the monetary value customers' assign to their offerings, and to estimate changes in this value from different market actions. As value to the firm is ultimately about the net present value of customers' economic contributions to the firm, this allows firms to balance value to the customer with value to the firm.